Estudo da capacidade funcional de idosos com neoplasias mieloides e leucemias agudas - Carbonell, Ana Lucia Ippolito [UNIFESP] (2013)
Introduction: The human aging has been accompanied by higher incidence and prevalence of myeloid neoplasms (MN). Hematologists use age, performance status (PS) and comorbidities indices to characterize the elderly patient. Improvement in the functional assessment can be achieved applying geriatric scales assessing functional status (FS). Objectives: To evaluate the functionality of elderly outpatients with MNs with scales utilized by hematologists and geriatricians. Thus, to study the impact of age, sex, comorbidities, and hemoglobin level in the functionality of such patients. Methods: Karnofsky (KPS), Eastern Cooperative Oncology Group (ECOG), the basic (ADL) and instrumental (IADL) activities of daily living scales were applied to assess the functionality of elderly outpatients with MN. The patients’ assessment was made by a hematologist and a geriatrician. The comorbidity index for hematopoietic cell transplantation (HCT–CI) was used to stratify the patients’ comorbidities. Statistical study applied the intraclass correlation, the alpha Cronbach’ coefficient, the Fisher tests, the t Student test and ANOVA. We fitted a mixed logistic regression model to evaluate the impact of age, sex, hemoglobin and comorbidities in performance and functional status of this group of elderly patients. Results: A total of 82 elderly patients (mean age of 72.8 years, varying from 60 to 90 years) were evaluated. Their hematological diagnosis included: essential thrombocythemia (ET; n=6); polycythemia vera (PV; n=15); chronic myeloid leukemia (CML; n=9); myelofibrosis (MF; n=25); myelodysplastic syndromes (MDS; n=17) and acute myeloid leukemia (AML; n=10). Eighty percent of the patients had good PS but only 50% of this group of individuals was independent in daily activities. All patients with poor PS were dependent in ADLs and/or IADLs. The mixed logistic regression models showed that age, sex, Hb and HCT–CI affected FS. However, only Hb and HCT–CI impacted on PS. Conclusions: The aggregation of the ADL and IADL to KPS and ECOG increases the sensibility and specificity of functional assessment of elderly patients with NM. The Hb level and comorbidity index affected both performance and functional status. However, the age and the sex only impacted on functional status.